Parcellised capital and underdevelopment a reinterpretation of the specific-factors model - De Dios, Emmanuel S. (1993)
Where capital markets are underdeveloped and political differences among capital owners predominate, capital becomes "parcellised" and is, for all intents and purposes, "specific" to the parcel. The familiar specific-factors model then becomes applicable. Parcellisation results in lower output and wages. Openness to world capital markets accentuates these effects as well as leads to the paradox of capital flight even from a capital-scarce country. Unproductive rent-seeking activities to defend one's parcel and to acquire others lead to a Cournot-Nash equilibrium which may be Pareto-inferior.
Keywords: Capital market; International trade; Capital movements